The Turks in world history - Findley, Carter V., 1941- (Oxford University Press, 2005)
Traces the Turkic peoples' trajectory from steppe, to empire, to nation-state. Unifying cultural, economic, social, and political history, this work illuminates the projection of Turkic identity across space and time and the profound transformations marked successively by the Turks' entry into Islam and into modernity.